Mesjid Tempat Ibadah yang Menyucikan Jiwa dan Menguatkan Spiritual - Fitratul Mubaraq; Maizal Efendi; Yova Murnika; Yohana Dwi Putri; Wismanto Wismanto (Moral : Jurnal kajian Pendidikan Islam, 2024)
Mosques have a very important role in the lives of Muslims, not only as places of worship but also as centers of spiritual and social development. This research aims to examine the function of mosques as places that purify the soul and strengthen spirituality. Through a qualitative approach using literature study methods, this research explores the role of mosques as centers of worship, character development, and strengthening social solidarity in the Muslim community. The research results show that mosques not only function as places of prayer, but also play a role in religious education, moral development, and social activities that strengthen relationships between believers. With its calm and peaceful atmosphere, the mosque is a place of reflection and contemplation, helping individuals draw closer to Allah and find inner calm amidst busy modern life.